A Bidirectional Two-Sample Mendelian Randomization Study of Genetic Causality Between Vitamin D Levels and Pemphigus - Wang Y; Cheng S; Que H (Clinical, Cosmetic and Investigational Dermatology)
Yanchun Wang,1 Shiping Cheng,2 Huafa Que3 1College of Clinical Medicine, Jiangxi University of Chinese Medicine, Nanchang, Jiangxi Province, People’s Republic of China; 2Department of Dermatology, the Affiliated Hospital of Jiangxi University of Chinese Medicine, Nanchang, Jiangxi Province, People’s Republic of China; 3Traditional Chinese Medicine Surgery, Longhua Hospital Affiliated to Shanghai University of Chinese Medicine, Shanghai, People’s Republic of ChinaCorrespondence: Huafa Que, Traditional Chinese Medicine Surgery, Longhua Hospital Affiliated to Shanghai University of Chinese Medicine, No. 725 Wanping South Road, Shanghai, 200032, People’s Republic of China, Email huafaque@126.comBackground: Pemphigus, a B-cell-mediated autoimmune disease, has been hypothesized to involve vitamin D due to its immunomodulatory effects on B-cell activity. However, observational studies on this association remain inconclusive due to confounding factors. This study used genome-wide association study (GWAS) data for bidirectional two-sample Mendelian randomization (MR) analysis to clarify causality.Materials and Methods: Genetic instruments for serum vitamin D levels (61 SNPs) and pemphigus (3 SNPs) were analyzed via inverse variance weighting (IVW), weighted median, and MR-Egger regression. Forward MR analysis revealed no causal effect of vitamin Don pemphigus risk [IVW OR=0.835 (95% CI:0.318– 2.189), P=0.623], consistent across sensitivity analyses. Conversely, reverse MR showed pemphigus did not influence vitamin D levels [IVW OR=1.000 (95% CI:0.993– 1.006), P=0.867]. Heterogeneity (Cochran Q test) and pleiotropy (MR-Egger intercept) tests confirmed robustness of results.Results: Our findings challenge the presumed causal link between vitamin D and pemphigus, suggesting observed associations may arise from confounding factors. This underscores the need for mechanistic studies to explore alternative pathways in pemphigus pathogenesis.Keywords: vitamin D, pemphigus, Mendelian randomization analysis, genome-wide association study